An in situ Gelling System Based on Methylcellulose and Tranilast Solid Nanoparticles Enhances Ocular Residence Time and Drug Absorption Into the Cornea and Conjunctiva - Nagai, Noriaki; Minami, Misa; Deguchi, Saori; Otake, Hiroko; Sasaki, Hiroshi; Yamamoto, Naoki (Frontiers in Bioengineering and Biotechnology, 2020)
We previously developed ophthalmic formulations containing tranilast nanopartaicles (ophthalmic TL-NPs formulations), and found them to show high uptake into ocular tissues. In this study, we aimed to design an in situ gel incorporating TL-NPs with 0.5–3% methylcellulose (MC, type SM-4) to ensure long residence time of the drug at the ocular surface. The ophthalmic TL-NPs formulations were prepared by the bead mill method, which yielded a mean particle size of ~93 nm with or without MC (0.5–3%). Although the dispersibility of TL particles in ophthalmic formulations increased with the MC content, the diffusion behavior of TL particles in the dispersion medium decreased with MC content. In an in vivo study using rats, the TL content in the lacrimal fluid was enhanced with MC content in the ophthalmic TL-NPs formulations, and the optimum amount of MC (0.5–1.5%) enhanced the TL content in the cornea and conjunctiva, and an anti-inflammatory effect of TL in rats instilled with ophthalmic TL-NPs formulations was observed. On the other hand, excessive MC (3%) prevented the corneal uptake of TL-NPs after instillation, and the anti-inflammation effect of TL was lower than that of ophthalmic TL-NPs formulations with optimum MC (0.5–1.5%). In conclusion, we found that gel formulations of TL-NPs with 0.5 and 1.5% MC provided a prolonged pre-corneal and pre-conjunctival contact time of TL, and resulted in higher TL contents in the cornea and conjunctiva following instillation in comparison with TL-NPs with or without 3% MC. This is probably due to the balance between the higher residence time and faster diffusion of TL-NPs on the ocular surface. These findings provide significant information that can be used to design further studies aimed at developing ophthalmic nanomedicines.